Health Care Provider Burnout in a United States Military Medical Center During a Period of War. Issue 2 (1st February 2016) - Sargent, Paul; Millegan, Jeffrey; Delaney, Eileen; Roesch, Scott; Sanders, Martha; Mak, Heather; Mallahan, Leonard; Raducha, Stephanie; Webb-Murphy, Jennifer
ABSTRACT: Objective: Provider burnout can impact efficiency, empathy, and medical errors. Our study examines burnout in a military medical center during a period of war. Methods: A survey including the Maslach Burnout Inventory (MBI), deployment history, and work variables was distributed to health care providers. MBI subscale means were calculated and associations between variables were analyzed. Results: Approximately 60% of 523 respondents were active duty and 34% had deployed. MBI subscale means were 19.99 emotional exhaustion, 4.84 depersonalization, and 40.56 personal accomplishment. Frustration over administrative support was associated with high emotional exhaustion and depersonalization; frustration over life/work balance was associated with high emotional exhaustion. Conclusions: Levels of burnout in our sample were similar to civilian medical centers. Sources of frustration were related to administrative support and life/work balance. Deployment had no effect on burnout levels.